Lugar do lixo é no lixo: estudo de caso de assimilação da informação - (:unkn) unknown (Universidade Federal do Rio de Janeiro / Instituto Brasileiro de Informação em Ciência e Tecnologia, 2003)
This present study investigates the assimilation of information: "the place for trash is in the trash" through the analysis of reports from three groups of students in the 4th grade of elementary school. For such, craft workshops of recycled paper of the projeto Recicloteca of non-governmental Organization - Ecomarapendi - were transformed in information aggregate and named experimental workshops. This type of approach defines its insertion on Information Science and its social responsibility with knowledge communication, has been woven a conceptual web joining threads of information and environmental education. Although there were barriers of communication, the results of the research show that the information was absorbed by a significant number of children which reveals the coherence and up-to-date-ness of this research in the problematic of solid waste - trash
Keywords: Assimilation of information; Environmental information; Trash; Assimilação da informação; informação ambiental; Craft Workshops of Recycled Paper; Lixo; Oficinas de reciclagem artesanal de papel; Environmental education; Educação ambiental; Ciência da informação